Gene Regulation Knows Its Boundaries. Issue 12 (December 2019) - de Wit, Elzo
Abstract : The genome is folded nonrandomly inside the cell nucleus. How this contributes to gene regulation is an important subject of investigation. A new study by Despang et al . shows how the spatial segregation of genes and regulatory regions can influence developmental expression in subtle, but critical ways.